EFL TEACHERS’ STRATEGIES IN TEACHING SPEAKING SKILL - Juliani - Putri Utami; Aunurrahman - Aunurrahman; Ageung - Daraja; Heti - Susanti (Journal of English Language Teaching and Education (JELTE), 2023)
This study aims to find out and get information about the strategies used by teachers in teaching speaking English. This research was conducted using a descriptive qualitative study. The subjects in this study were 2 English teachers at SMA Karya Sekadau. In collecting data, researchers used observation blueprints, and field notes to record observations in research, and in data collection techniques researchers used, observation, questionnaires, and tryouts to obtain more valid information regarding the steps and strategies used by teachers in teaching speaking. English. Researchers also use thematic analysis to determine the meaning and theme of the research subject and can interpret it in the text. Based on the data, it was found that the strategies that were often used by teachers when teaching English Speaking in class includes role-playing, talking about games and graphics, and discussing strategies. Teachers employ this tactic more frequently to encourage student participation in class discussions. The approach is applicable to learning to speak English, thus that is the conclusion that may be reached. Students can converse more fluently in English as a result.